Surface albedo feedbacks from climate variability and change. Issue 7 (11th April 2013) - Colman, R. A.
Abstract: [1] Snow and sea ice surface albedo feedback is evaluated in models from the World Climate Research Program Coupled Model Intercomparison Project phase 3 using the radiative "kernel" technique. A comparison is carried out between feedbacks at climate change timescales and those operating under seasonal, interannual, and decadal variability. A primary motivation is to examine possible relationships across these timescales. Similarities are found in the mean model meridional distribution of feedback, although uncertainties are large due to model spread and uncertainties from regressions. Climate change feedback appears stronger over the Arctic north of 75°N. Consistent with findings elsewhere, climate change feedback strengths over Northern Hemisphere (NH) snow and sea ice are uncorrelated, although a weak correlation is found between NH and Southern Hemisphere (SH) sea ice. By contrast, at other timescales, moderate positive correlations are found between NH snow and sea ice albedo feedbacks, as well as between NH and SH sea ice albedo feedbacks. Statistically significant correlations are not found between surface albedo feedbacks at climate change and other timescales, either for global feedback or for NH and SH sea ice. Notably, however, correlations are found for NH snow albedo feedback against both seasonal and interannual feedbacks. This suggests that NH snow albedo feedback is a "special case, " potentially revealing short‐term analogues appropriate for close comparison with climate change, with such relationships not holding for other components of the surface albedo feedback. Key Points: Evaluates surface albedo feedback in GCMs at a range of timescales Feedbacks show similarities in structure and strength across timescales Only northern hemisphere snow feedbacks are correlated with climate change